Increased intramuscular adipose tissue of the quadriceps is more strongly related to declines in ADL than is loss of muscle mass in older inpatients. Issue 3 (March 2021) - Akazawa, Naoki; Kishi, Masaki; Hino, Toshikazu; Tsuji, Ryota; Tamura, Kimiyuki; Moriyama, Hideki
Summary: Background & aims: Recent studies have shown that increased intramuscular adipose tissue of the quadriceps in older people is more strongly related to decreased muscle strength, sit-up and sit-down ability, and gait ability than is loss of muscle mass. However, whether increased intramuscular adipose tissue of the quadriceps is more strongly related to declines in activities of daily living (ADL) than is loss of muscle mass in older inpatients remains unclear. This study was performed to examine the relationships of intramuscular adipose tissue and muscle mass of the quadriceps with ADL in older inpatients. Methods: This cross-sectional study included 371 inpatients aged ≥65 years. The primary outcomes were ADL and intramuscular adipose tissue of the quadriceps. ADL were assessed using the motor-Functional Independence Measure (FIM). Ultrasound images were acquired using B-mode ultrasound imaging. Intramuscular adipose tissue and muscle mass of the quadriceps were assessed based on echo intensity and muscle thickness, respectively. A stepwise multiple regression analysis was performed to identify factors independently associated with the motor-FIM score. The independent variables were the echo intensity and muscle thickness of the quadriceps, age, sex, length of hospital stay, Food Intake Level Scale (FILS), Geriatric Nutritional Risk Index (GNRI) score, C-reactive protein (CRP) concentration, updated Charlson comorbidity index (UCCI), number of medications, and subcutaneous fat thickness of the thigh. Results: Quadriceps echo intensity (β = − 0.17), FILS (β = 0.38), GNRI score (β = 0.24), UCCI (β = − 0.16), subcutaneous fat thickness of the thigh (β = − 0.11), and length of hospital stay (β = 0.09) were independently and significantly associated with the motor-FIM score. Quadriceps thickness (β = 0.10), age (β = − 0.07), sex (β = − 0.04), CRP concentration (β = − 0.04), and number of medications (β = 0.03) were not associated with the motor-FIM score. Conclusions: Increased intramuscular adipose tissue of the quadriceps is more strongly related to declines in ADL than is loss of muscle mass. Randomized controlled trials are needed to determine whether decreasing intramuscular adipose tissue of the quadriceps in older inpatients leads to improvement of ADL.